NYPD confidential : power and corruption in the country's greatest police force - Levitt, Leonard, 1941- (New York : Thomas Dunne Books, 2009)
Examines the rivalry of New York City's police commissioner and mayor for control over and credit for the city's police force, identifying disturbing cover-ups and corrupt practices that are undermining the NYPD's effectiveness and honor.
Evidence of things not seen -- The secret meeting -- The rise of Bill Bratton -- The dirty thirty -- The fall of Bill Bratton -- Get on the train or get under it -- The tragedies of Abner Louima and Amadou Diallo -- How well do you know Bernie Kerik? -- Never appoint a bitter man police commissioner.
Includes bibliographical references (p. [289]-290) and index.
Keywords: Police corruption -- New York (State) -- New York -- History; Police administration -- New York (State) -- New York -- History; Police -- New York (State) -- New York -- History